Effect of Apricot Fruit and Kernel Extracts on in-vitro Dissolution of Cholesterol Gallstones: Implication for Development of Potent Anti-cholilithiaticc agent - Tiwari, Sunita Waila; Sah, Archana Negi (Indian Journal of Pharmaceutical Education and Research, 2020)
Prunus armeniaca L. (apricot) belonging to family Rosaceae is an important edible medicinal plant containing many important constituents like polysaccharides, polyphenol, fatty acid and carotenoids. In this study, we attempted to assess the in-vitro anti-gall bladder stones activity (anticholilithiatic activity) of Prunus armeniaca L. (apricot) kernel and fruit extracts. Methodology: For this study, some human gall bladder stones (cholesterol and pigment stones) along with human bile, were collected from hospitals, incubated in human bile and treated with a combination of apricot fruit and kernel extracts in two doses (1mg/ml and 2 mg/ml) and standard drug (ursodiol, 2 mg/ml) for 4 weeks. Dried weight of gallstones and the amount of cholesterol released, before and after treatment were calculated. Results: From this experiment, it was found that the dried weight of cholesterol gallstones was reduced and the amount of cholesterol released from gallstones was increased in a dose-dependent manner, due to the effect of extracts. Morphological changes like color and fragility in gall stones were also observed due to the effect of extracts. Conclusion: This in-vitro study has given the primary evidence that the combination of apricot kernel and fruit extracts may cause the complete dissolution of cholesterol gallstones thus have the anti-cholilithiatic activity. Further in-vivo studies can be carried out on these extracts of apricot.
Keywords: Cholelithiasis; Gallstones; Kernel; Ursodiol; Prunus armeniaca L